Molecular cytogenetic characterization of five F8 complex rearrangements: utility for haemophilia A genetic counselling. Issue 4 (5th May 2017) - Jourdy, Y.; Chatron, N.; Fretigny, M.; Carage, M. L.; Chambost, H.; Claeyssens‐Donadel, S.; Roussel‐Robert, V.; Negrier, C.; Sanlaville, D.; Vinciguerra, C.
Abstract : Background: Genomic inversions are usually balanced, but unusual patterns have been described in haemophilia A (HA) patients for intron 22 (Inv22) and intron 1 (Inv1) inversions leading to the hypothesis of more complex rearrangements involving deletions or duplications. Aim: To characterize five abnormal patterns either in Southern blot and long‐range PCR for Inv22 or in PCR for Inv1. Materials and methods: All patients were studied using cytogenetic microarray analysis (CMA). Results: In all cases, CMA analysis found that each inversion was associated with complex Xq28 rearrangement. In three patients, CMA analysis showed large duplication ranging from 230 to 1302 kb and encompassing a various number of contiguous genes among which RAB39B . RAB39B duplication is a strong candidate gene for X‐linked intellectual disability (XLID). Surprisingly, none of the severe HA patients with RAB39B duplication reported in this study or in the literature exhibited XLID. We hypothesise that F8 complex rearrangement down regulated RAB39B expression. In the two remaining patients, CMA analysis found Xq28 large deletion (from 285 to 522 kb). Moyamoya syndrome was strongly suspected in one of them who carried BRCC3 deletion. Conclusion: Because several F8 neighbouring genes are associated with other pathologies such as XLID and cardiovascular disease, all HA patients where complex Xq28 rearrangement was suspected should be referred to a geneticist for possible utility of a pangenomic study. Such investigation should be carefully considered in genetic counselling in female carriers to assess the risk of transmitting severe HA with a "contiguous gene syndrome".